QUALITATIVE STUDY REGARDING THE EVOLUTION OF PUBLIC INVESTMENTS AND PRIVATE INVESTMENTS - Daniela STANCU (ZAMFIR) (Challenges of the Knowledge Society)
In this written paper I will conduct a qualitative research on the evolution of public investments and the evolution of private investments. Qualitative research in the field of public investment and in the field of private investment is introductory and I must say it necessary to go through a few steps: a short introduction; it is important to show the types of qualitative research methods designed in this way and those that have led to the perception of the target audience and the disclosure of the behavior of the target audience; then the research objectives and qualitative research procedures in the field of investments and their applications are established, the outline of the research methodology and the analysis of the details and results, as well as the highlighting of the conclusions.